Syntactical Evidence of Aramaic Sources in Acts I-XV - Martin, Raymond A. (New Testament studies, 1964)
Source criticism in Acts has had a long and varied history. While one can hardly speak of a consensus of opinion on the question today, certain trends are evident. The present tendency is to study the smaller units of Acts, rather than to seek for continuous sources throughout the book. In this development can be seen the influence of M. Dibelius's 1923 essay on the ‘style criticism’ of Acts.